Catalogue of the world genera and subgenera of the superfamilies Derodontoidea and Bostrichoidea (Coleoptera: Derodontiformia, Bostrichiformia) - Zahradník, Petr; Háva, Jiří (Zootaxa, 2014)
A catalogue of all the known genera and subgenera of the Coleoptera series Derodontiformia and Bostrichiformia, each with a single superfamily (Derodontoidea and Bostrichoidea, respectively), is provided. The following new tribes are established and type genera are designated: Apphianini Háva trib. nov., Ranolini Háva trib. nov. (all Dermestidae); Ochinini Zahradník trib. nov., Phanerochilini Zahradník trib. nov. (all Ptinidae). The subgenus Paranovelsis has been removed as a synonym and has been reelevated to generic rank. The following new synonymies are proposed: Megatoma Herbst, 1791 (= Perimegatoma Horn, 1875 syn. nov., Caucasotoma Mroczkowski, 1967 syn. nov.); Trinodes Dejean, 1821 (= Trinodus Gistl, 1856 syn. nov.); Nosodendron Latreille, 1804 (= Nosodendrium Gistl, 1856 syn. nov.); Casapus Wollaston, 1862 (= Pithodes Wollaston, 1862 syn. nov.).